Are We "There" Yet?: A Comparative Analysis of the Canadian Standards on the Corporal Punishment of Children in Schools - Caroline Locher-Lo (Athens Institute for Education and Research, 2018)
In 1973, British Columbia (B.C.) became the first province in Canada to forbid corporal punishment in public schools (B.C. School Act), followed by the majority of the other provinces. Alberta and Manitoba however, still have no provincially enacted legal prohibition, although many school boards have updated their policies to state that corporal punishment should be prohibited. The spotlight on efforts to repeal Section 43 of the Criminal Code may have dimmed over time on the national stage, but the recent Canadian Truth and Reconciliation report has ignited this issue once again. My article explores the existing laws with a comparative approach (Reimann & Zimmermann, 2008; Orucu & Nelken, 2007), in terms of where Canada stands in relation to other nations' legislative standards and practices. It also addresses the severe behavioural and psychological implications on impacted children. As a developed nation, Canada needs to reconsider its current state of "progress" by inspecting and reviewing existing discourses and legislatives to ensure successful prevention of corporal punishment in schools. This paper intends not only to contribute to the advancement of Canadian legislative standards, but also to practices in local and international education.